2020
DOI: 10.28945/4540
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Identity Work in a Professional Facebook Group

Abstract: Aim/Purpose: The aim of this study is to investigate posts that deviate from the norm by receiving many more comments than likes in a teacher thematic Facebook (FB) group. Background: Social media sites are currently becoming standard tools for professional practices. Swedish teachers use thematic FB groups as a platform for professional learning. Methodology: Data from a large teacher FB group over a three-year period have been collected using programmatic approaches. The interactions have been analysed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…They also reported that Facebook was relatively beneficial to their professional life (Bergviken Rensfeldt et al, 2018). In another study, Swedish teachers reported that they share teaching material and resources and give and receive emotional and professional support (Lundin et al, 2020). Moreover, teachers' responses to the survey questions about the impact of participating in ESL FTPs in this study are similar to students' and teachers attitudes towards professional discussion forums on the Internet and Online Learning Management Systems, and professional groups on other social media such as Twitter (Al-Jarf, 2005;Al-Jarf, 2006a;Al-Jarf, 2006b;Al-Jarf, 2006c;Al-Jarf, 2007a;Al-Jarf, 2007b;Al-Jarf, 2014;Al-Jarf, 2017;Al-Jarf, 2020a;Al-Jarf, 2020b).…”
Section: Dmentioning
confidence: 99%
See 3 more Smart Citations
“…They also reported that Facebook was relatively beneficial to their professional life (Bergviken Rensfeldt et al, 2018). In another study, Swedish teachers reported that they share teaching material and resources and give and receive emotional and professional support (Lundin et al, 2020). Moreover, teachers' responses to the survey questions about the impact of participating in ESL FTPs in this study are similar to students' and teachers attitudes towards professional discussion forums on the Internet and Online Learning Management Systems, and professional groups on other social media such as Twitter (Al-Jarf, 2005;Al-Jarf, 2006a;Al-Jarf, 2006b;Al-Jarf, 2006c;Al-Jarf, 2007a;Al-Jarf, 2007b;Al-Jarf, 2014;Al-Jarf, 2017;Al-Jarf, 2020a;Al-Jarf, 2020b).…”
Section: Dmentioning
confidence: 99%
“…Unlike the current study which revealed a wide range of topics posted in TFPs, the topics on which a Swedish teacher thematic Facebook group focused were less comprehensive than those in the current study. Lundin et al (2020) reported that the posts Swedish teacher thematic Facebook group were questions and/or requests that focused on four themes: sharing, pedagogical ideas and premises, instructionally motivated technical features, and functionally motivated technical features.…”
Section: Improve Your Conversation Skills (Video) English Writing Les...mentioning
confidence: 99%
See 2 more Smart Citations
“…FL literature is presently dominated by investigated FL cases and FL effectiveness (Lundin et al 2020). As Lundin et al (2020) found, in the initial years of FL research, descriptive case reports on FL implementation were dominant, but these studies were mainly limited to reporting the experimental process and results of adopting FL in individual courses or subjects at individual schools. There have also been studies with reflection or opinion-based arguments around FL and with a theoretical approach discussing relevant educational theories supporting FL (Lundin , 2020).…”
Section: Growth Of Flipped Learning Researchmentioning
confidence: 99%